Genomic diversity and taxonomic marker for Arcobacter species - Zhou, Guilan; Gu, Yixin; Wang, Hairui; Chen, Xiaoli; Zhang, Xin; Shao, Zhujun; Yan, Xiaomei; Zhang, Jianzhong; Zhang, Maojun (Frontiers in Microbiology, 2023)
Arcobacter was recognized as an emerging enteropathogen and controversies regarding its classification persisted. This study aimed to reevaluate the taxonomy of Arcobacter utilizing the 16S rRNA gene, 23S rRNA gene, single-copy orthologous genes, as well as genomic indices such as Average Nucleotide Identity (ANI) and in silico DNA-DNA hybridization (isDDH). The taxonomy of this genus was reevaluated in this study using multiple indices with a dataset of 371 genomes comprising 34 known species and 14 potentially new species. Good discrimination could be achieved only in some species but not for the species with higher sequence similarity using the comparisons of the 16S rRNA gene and 23S rRNA gene sequences. A high-accuracy phylogenomic approach for Arcobacter was established using 84 single-copy orthologous genes obtained through various bioinformatics methods. One marker gene (gene711), which was found to possess the same distinguishing ability as ANI, isDDH, 删除了: sequences 29 删除了: on 30 and single-copy orthologous methods, was identified as a reliable locus for inferring the phylogeny of the genus. The effective species classification was achieved by employing gene711 with a sequence similarity exceeding 96%, even for species like A. cloacae, A. lanthieri, and A. skirrowii, which exhibited ambiguous classification using ANI and isDDH. Additionally, excellent subspecies categorizing among A. cryaerophilus could be distinguished using gene711. In conclusion, this framework strategy had the potential advantage of developing rapid species identification, particularly for highly variable species, providing a novel insight into the behavior and characteristics of Arcobacter.